1998
DOI: 10.1002/(sici)1097-4636(199802)39:2<292::aid-jbm17>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microstructure on the corrosion behavior of CoCr porous coatings on orthopedic implants

Abstract: Cobalt-chromium alloy porous coatings have become increasingly popular as a means of achieving a stable, longer lasting fixation on orthopedic implants. However, sintering heat treatments cause changes in the microstructure that result in changes in the corrosion behavior of the porous coatings. Experiments were conducted to examine the effects of microstructure on the corrosion of CoCr porous coatings. Four distinct microstructures were characterized. Light microscopy revealed microstructures A and B had rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…These carbides have excellent corrosion resistance at the expense of the matrix which has been partially leached of its primary corrosion resistant additive, chromium [63]. This process, known as sensitization, causes the chromium deprived areas to become favorable sites for localized corrosion attack [32]. Although the primary purpose of Co-Cr homogenizing solution treatments is to improve the poor mechanical properties seen in the as-cast state, the resulting microstructure homogenization has also been found by various groups to increase localized corrosion resistance.Ti-6Al-4V is not prone to sensitization-like effects as seen in Co-Cr.…”
Section: Sensitization Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…These carbides have excellent corrosion resistance at the expense of the matrix which has been partially leached of its primary corrosion resistant additive, chromium [63]. This process, known as sensitization, causes the chromium deprived areas to become favorable sites for localized corrosion attack [32]. Although the primary purpose of Co-Cr homogenizing solution treatments is to improve the poor mechanical properties seen in the as-cast state, the resulting microstructure homogenization has also been found by various groups to increase localized corrosion resistance.Ti-6Al-4V is not prone to sensitization-like effects as seen in Co-Cr.…”
Section: Sensitization Effectmentioning
confidence: 99%
“…In the case of solution treated cast Co-Cr, care must be taken to avoid undoing the advantages offered by solution treatment i.e. reprecipitating the various second phases and inducing further grain growth [32]. The work strengthened nature of wrought Co-Cr means that the exposure to the high temperatures required for the coating application will release all the stored deformation energy, negating the advantages provided by wrought processing [20,33].…”
Section: Porous Coating Applicationmentioning
confidence: 99%
“…3) Therefore, the porous Co-Cr-Mo coating on the implants as well as the substrate Co-Cr-Mo alloy, should not contain Ni since the release of metal ions at the large interface between body fluid and metal 4) presents great concern.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ion-release mechanism has shown that the amounts of each element released were not proportional to the composition in all cases. 8,9 Furthermore, it has been indicated that corrosion rates of CoCr implant alloys in vivo are much faster than in vitro. 10 To solve the above problems, such as wear debris and ion release, some improvements have been accomplished.…”
Section: Introductionmentioning
confidence: 99%